2017
DOI: 10.1037/drm0000053
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nursing students regarding sexual dreams.

Abstract: The aim of this study was to describe the experiences related to sexual dreams in a sample of nursing degree students from the University of Almería, Spain. The research instrument used was an adapted version of the Sexual Dream Experience Questionnaire. This questionnaire is composed of 32 items, divided into 4 dimensions: Joyfulness, Aversion, Familiarity, and Bizarreness. The main results highlighted differences in relation to sex-men have more sexual dreams than women and place more importance on them. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(44 reference statements)
2
2
0
Order By: Relevance
“…People often reported sexual pleasure and emotional satisfaction during or after sexual dreams (Gutiérrez-Puertas et al, 2017;Younis et al, 2017;Yu, 2013), which supported our result that sDreamers scored higher on Joyfulness (i.e., the happiness and satisfaction with sexual dreams). Higher Familiarity (i.e., the familiar scenes appeared in sexual dreams) in sDreamers was in accordance with the continuity hypothesis of dreaming (Domhoff, 1999(Domhoff, , 2003 as well as with the finding that the most common targets involved in sexual dreams were friends or acquaintances or both of that individual (King et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…People often reported sexual pleasure and emotional satisfaction during or after sexual dreams (Gutiérrez-Puertas et al, 2017;Younis et al, 2017;Yu, 2013), which supported our result that sDreamers scored higher on Joyfulness (i.e., the happiness and satisfaction with sexual dreams). Higher Familiarity (i.e., the familiar scenes appeared in sexual dreams) in sDreamers was in accordance with the continuity hypothesis of dreaming (Domhoff, 1999(Domhoff, , 2003 as well as with the finding that the most common targets involved in sexual dreams were friends or acquaintances or both of that individual (King et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Previous literature showed that frequency of sexual dreams was related to the sexual fantasies in waking time (Schredl et al, 2009). Sexual dream functioned as a positive manifestation of sexuality and perhaps fulfilled individual’s unsatisfied sexual desires during waking state, for instance, people often felt satisfied after having sexual dreams (Gutiérrez-Puertas et al, 2017; Younis et al, 2017). However, deviant sexual dreams that influence one’s sleep quality and cause sleep problems might affect physical and mental health adversely (Manocchia et al, 2001; Stein et al, 2008).…”
mentioning
confidence: 99%
“…However, ∼16% of men and 18% of women reported experiencing erotic dreams “often” or “very often,” which support that these sexually related dreams are usual. Although the lack of a significant sex difference in the prevalence of erotic dreams contrasts with results from some studies (Gutiérrez-Puertas et al, 2017; Schredl et al, 2009), it is consistent with findings from Canadian samples (Zadra, 2007; Zanasi et al, 2012). Thus, cultural differences surrounding sexuality and open attitudes may be at play in the general prevalence rate of sexual dreams in men and women.…”
Section: Discussionsupporting
confidence: 86%
“…One important finding on the content of sexually toned dreams is that only a minority of these dreams include the dreamer’s current or past romantic partners (Clarke et al, 2010; Zadra, 2007; Zadra & Gervais, 2011). In fact, in ∼70% of women’s erotic dreams and up to 90% of men’s erotic dreams, the identified sexual target is not the dreamer’s current sex partner, but rather another character such as an acquaintance, colleague, stranger, or public figure (Gutiérrez-Puertas et al, 2017; King et al, 2009; Yu, 2013; Zadra, 2007). Even in individuals involved in a committed relationship, research shows that the dreamer’s current partner only figures in about a third of reported sexual dreams (King et al, 2009; Younis et al, 2017).…”
mentioning
confidence: 99%